Impacts of Climate Change on Mountaineering Routes in the Écrins Massif (Western Alps, France) - Mathis Arnaud; Jacques Mourey; Philippe Bourdeau; Richard Bonet; Ludovic Ravanel (Revue de Géographie Alpine)
Mountaineering is one of the most affected sports activities due to the current climate crisis and the resulting changes in the physical environment of the high mountain areas. Some routes have disappeared while others are no longer accessible in summer (hazards, technical difficulties, etc.). Research has already been conducted on the impact of climate change on mountaineering and on adaptation. The Mont-Blanc massif and the Valais Alps have been used as study areas to understand the evolution of mountaineering routes over recent decades. A mapping of the geomorphological and glaciological processes affecting mountaineering routes has been conducted for the Valais. This study aims to apply this method to Écrins massif (French Alps), which had so far remained unstudied despite its emblematic character. The famous topo-guide "Le massif des Écrins - Les 100 plus belles courses et randonnées" (1974) was used as a basis for the study with 70 routes being selected according to their notoriety and visitor numbers. All the processes affecting the routes were mapped using GIS, and a statistical analysis was carried out to gain a better understanding of the evolution of the routes, together with semi-directive interviews with experts and practitioners. A new process – the early summer melting of ice and snow cover – was identified. As is the case in the Mont-Blanc massif and the Valais, a route is affected by 9 processes on average, and almost 25% of the routes can no longer be climbed in summer. The mapping method has been successfully applied to Écrins massif, providing new knowledge of the recent evolution of mountaineering routes in the Alps.